Popliteal artery entrapment syndrome - O'Leary, D.P. (2010)
Popliteal artery entrapment syndrome is a rare abnormality of the anatomical relationship between the popliteal artery and adjacent muscles or fibrous bands in the popliteal fossa. The following is a case report of a 19 year old female, in whom popliteal artery entrapment syndrome was diagnosed, and successfully treated surgically. A review of literature is also presented and provides details on how PAES is classified, diagnosed both clinically and radiologically, and treated surgically.